Ecocide in Maqashid Shariah Review - Hasyim, Muhammad (Journal of Education and Religious Studies, 2024)
Ecocide is a destructive action against the ecosystem that has a wide impact on human life and the environment. This article aims to describe and analyze Ecosida in an Islamic perspective, which is specifically studied in maqashid sharia. The method used in this study is the literature method, where data is taken from various primary and secondary references, then analyzed using content analysis techniques. The results of the study show that ecocide damages the ecological balance which is an important prerequisite for the fulfillment of sharia maqashid. Environmental damage threatens the health, intellectual potential, sustainability of future generations, and the well-being of humanity. In addition, destructive actions against the environment hinder the implementation of worship and damage the spiritual relationship of humans with Allah SWT. Therefore, strengthening the understanding of sharia maqashid in an ecological context is very important. This research recommends the integration of Islamic values in education and da'wah to build collective awareness in environmental conservation. Thus, Muslims can take an active role as caliph fil ard in maintaining the sustainability of the ecosystem and realizing common benefits for current and future generations.